A review on the preparation of thin-film YSZ electrolyte of SOFCs by magnetron sputtering technology - Yang, Ying; Zhang, Yanxiang; Yan, Mufu (Separation and purification technology, 2022)
[Display omitted] •The feasibility of preparing YSZ electrolyte thin films by different methods was evaluated.•Process optimization for improving the density of YSZ thin films prepared by magnetron sputtering.•The electrochemical performance of SOFCs can be further improved by applying bilayer or multilayer electrolytes.•The preparation of large-area thin films with complex compositions by magnetron sputtering is the future development direction of thin-film SOFCs. Solid oxide fuel cells (SOFCs) have become one of the most attractive energy conversion devices due to their fuel flexibility, environmental friendliness and promising energy conversion efficiency. However, the high operating temperature (typically above 800 °C) of SOFCs poses some challenges concerning stability, sealing integrity and safety. Reducing the operating temperature of SOFCs to 600 °C or lower is currently an important research topic in the field. One effective strategy is to reduce the thickness of the electrolyte with high stability and high performance at lower temperatures. Among the thin-film preparation technologies, magnetron sputtering is gaining attention due to the advantages in scaling up and commercialization. Here we compare and analyze various electrolyte preparation methods and present a comprehensive review of the preparation of oxygen-ion-conducting electrolyte thin films by magnetron sputtering technology. The yttria-stabilized zirconia (YSZ) electrolyte and YSZ-based bilayer or multilayer electrolyte are employed as examples due to their high stability and high ionic conductivity. The effects of processing parameters on the microstructures and properties of the electrolyte thin films, the relevant interfaces and full SOFCs are reviewed and discussed. Finally, we present some perspectives and directions for developing high-performance SOFCs with thin-film electrolytes prepared by magnetron sputtering technology.